Sleepy bears - Fox, Mem, 1946-; Argent, Kerry, 1960- (San Diego : Harcourt, 2002)
When winter comes, six sleepy bears are rhymed to sleep by Mother Bear.
"Voyager Books.".
Pub Weekly.
School Library Journal.
Wilson's Children.
3-7.
3.4
Keywords: Bears -- Juvenile fiction; Bedtime -- Juvenile fiction; Mother and child -- Juvenile fiction; Sleep -- Juvenile fiction; Bears -- Fiction; Bedtime -- Fiction; Mother and child -- Fiction; Sleep -- Fiction; Bears -- Fiction; Bedtime -- Fiction; Mother-child relationship -- Fiction; Sleep -- Fiction